Economic Geography and Economic Development in Sub-Saharan Africa - Bosker, Maarten (Oxford University Press on behalf of the World Bank, 2014)
Sub-Saharan Africa's (SSA) physical geography is often blamed for its poor economic performance. A country's geographical location does, however, not only determine its agricultural conditions or disease environment. It also pins down a country's relative position vis-à-vis other countries, affecting its ease of access to foreign markets. This paper assesses the importance of market access for manufactures in explaining the observed income differences between SSA countries over the period 1993–2009. We construct yearly, theory-based measures of each SSA country's market access using the information contained in bilateral manufacturing trade flows. Using these measures, we find a robust positive effect of market access on economic development that has increased in importance during the last decade. Interestingly, when further unraveling this finding, access to other SSA markets in particular turns out to be important.